Surface-activation modified perovskite crystallization for improving photovoltaic performance. (September 2017) - Tong, Guoqing; Lan, Xinzheng; Song, Zihang; Li, Guopeng; Li, Huan; Yu, Linwei; Xu, Jun; Jiang, Yang; Sheng, Yun; Shi, Yi; Chen, Kunji
Abstract: An improved vapor-phase deposition that leveraged the use of surface activation of PbI2 film has been developed for modifying perovskite crystallization process. This was achieved by loading Cl − ligands on closely-packed PbI2 particle film—a scaffold that allowed in situ formation of perovskite active layer. The introducing of Cl − ligands served the Cl-capped and thus electrostatically-charged PbI2 nanoparticles showed improved colloidal stability in DMF, which facilitated the preparation of PbI2 film. More importantly, during the process of CH3 NH3 I (MAI) deposition i.e. the growth of perovskite materials, the presence of three-dimensional Cl − ligand matrix favored the formation of dense perovskite film. Moreover, a desired release of chloride was also achieved, thus promote the rearrangement of the perovskite during the volume expansion process. This finally led to a PCE of PSCs exceeding 16.42% under AM 1.5 irradiation. Therefore, surface-activation with Cl-ligand matrix could provide guidelines for the morphology optimization and the perovskite devices performance enhancement. Graphical abstract: The NH4 Cl was introduced as additive to realize Cl − ligands on closely-packed PbI2 particle film, and favor the formation of dense perovskite film in subsequence chemical vapor deposition. An impressive power conversion efficiency of 16.42% was obtained with the NH4 Cl:PbI2 ratio of 0.75. The results showed that the release of chloride promotes the rearrangement of the perovskite during the volume expansion process, meanwhile the chloride was also introduced into the perovskite crystal structure to form the CH3 NH3 PbI3 and CH3 NH3 PbI3-x Clx phase, reducing the hysteresis effect in the devices. Therefore, surface-activation with Cl-ligand matrix could provide guidelines for the morphology optimization and also a promising method for the perovskite devices performance enhancement. Highlights: The PbI2 is dissolved completely at the room temperature and shows a high crystallization morphology with the NH4 Cl inclusion. The ligand matrix offers activated surface for the perovskite deposition and effectively reduces the deposition time. The Cl − was introduced into the perovskite film to form the CH3 NH3 PbI3 and CH3 NH3 PbI3-x Clx, reducing the hysteresis effect. The perovskite solar cell exhibits a high PCE of 16.42% with the NH4 Cl:PbI2 ratio of 0.75.